The Metabolic Changes and Immune Profiles in Patients With COVID-19 - He, Bing; Wang, Jun; Wang, Yudie; Zhao, Juan; Huang, Juan; Tian, Yu; Yang, Cheng; Zhang, Heng; Zhang, Mingxia; Gu, Lixing; Zhou, Xiaocui; Zhou, Jingjiao (Frontiers in Immunology, 2020)
To explore the metabolic changes and immune profiles in patients, we analyzed the data of patients with mild and severe COVID-19. Forty-seven percent (IQR, 33-59) of leukocytes were lymphocytes (2.5×109/L (IQR, 2.2-3.3)) and monocytes were 0.51×109/L (IQR, 0.45-0.57) in young children with COVID-19. In 32 mild COVID-19 patients, circulating monocytes were 0.45×109/L (IQR, 0.36-0.64). Twenty-one severe patients had low PO2 (57 mmHg (IQR, 50-73)) and SO2 (90% (IQR, 86-93)), and high lactate dehydrogenase (580 U/L (IQR, 447-696)), cardiac troponin I (0.07 ng/mL (IQR, 0.02-0.30)), and pro-BNP (498 pg/mL (IQR, 241-1726)). Serum D-dimer and FDP were 9.89 mg/L (IQR, 3.62-22.85) and 32.7 mg/L (IQR, 12.8-81.9), and a large number of RBC (46/μL (IQR, 4-242) was presented in urine, a cue of disseminated intravascular coagulation (DIC) in severe patients. Three patients had comorbidity with diabetes, and 18 patients without diabetes also presented high blood glucose (7.4 mmol/L (IQR, 5.9-10.1)). Fifteen of 21 (71%) severe cases had urine glucose +, and 9 of 21 (43%) had urine ketone body +. The increased glucose was partially caused by reduced glucose consumption. Severe cases had extraordinarily low serum uric acid (176 μmol/L (IQR, 131-256)). In the late stage of COVID-19, severe cases had extremely low CD4+ T cells and CD8+ T cells, but unusually high neutrophils (6.5×10⁹/L (IQR, 4.8-9.6)), procalcitonin (0.27 ng/mL (IQR, 0.14-1.94)), C-reactive protein (66 mg/L (IQR, 25-114)) and an extremely high level of interleukin-6. Four of 21 (19%) severe cases had co-infection with fungi, and 2 of 21 (9%) severe cases had bacterial infection. Our findings suggest that, severe cases had acute respiratory distress syndrome (ARDS) Ⅰ-Ⅲ, and metabolic disorders of glucose, lipid, uric acid, etc., even multiple organ dysfunction (MODS) and DIC. Increased neutrophils and severe inflammatory responses were involved in ARDS, MODS, and DIC. With the dramatical decrease of T-lymphocytes, severe cases were susceptible to co-infect with bacteria and fungi in the late stage of COVID-19. In young children, extremely high lymphocytes and monocytes might be associated with the low morbidity of COVID-19. The significantly increased monocytes might play an important role in the recovery of patients with mild COVID-19.